'The Ostrich Problem': Motivated Avoidance or Rejection of Information About Goal Progress. Issue 11 (4th November 2013) - Webb, Thomas L.; Chang, Betty P. I.; Benn, Yael
Abstract: Monitoring one's current standing with respect to goals can promote effective self‐regulation. However, the present review suggests that there is an ostrich problem such that, in many instances, people have a tendency to "bury their head in the sand" and intentionally avoid or reject information that would help them to monitor their goal progress. For example, people with diabetes avoid monitoring their blood glucose, and few people monitor their household energy consumption, check their bank balances, keep track of what they are eating and so on. While situational constraints can explain some problems with progress monitoring, we use a self‐motives framework to posit that the decision to avoid monitoring often represents the product of an interaction between different motives. For example, the desire to accurately assess progress may conflict with the desire to protect or enhance the self. The present review collates evidence pertaining to the ostrich problem, identifies different motives that underlie the decision to monitor versus not monitor goal progress, illustrates how the ostrich problem might be integrated into models of self‐regulation, and provides suggestions for future research. In so doing, the review advances our understanding of the nature and determinants of intentionally deficient monitoring.